Charakterisierung und Modellierung der Steifigkeit von langfaserverstärktem Polypropylen - Brylka, Bartholomäus (Schriftenreihe Kontinuumsmechanik im Maschinenbau / Karlsruher Institut für Technologie, Institut für Technische Mechanik - Bereich Kontinuumsmechanik, 2017)
Dynamical mechanical analysis is used to investigate the temperature dependent, anisotropic visco-elastic stiffness, damage induced stiffness degradation as well as physical aging of polypropylene and the anisotropic compression molded long fiber reinforced polypropylene. Based on micro-computer tomography data, the approximations of the linear elastic properties using the Mori-Tanaka method are presented.